Promoting oral health in elementary schools: The effectiveness of dental stand media - Dita Syifa Khairunnisa; Ria Pangestu Ramadhani; Nura Syifa Ristika Ayu Putri; Dwi Aji Nugroho; Sri Utami; Sartika Puspita (Community Empowerment, 2024)
Oral and dental health is a common health problem experienced by various segments of Indonesian society but is often neglected. Approximately 57.6% of the population experiences oral and dental health problems, but only 10.2% receive treatment from dental professionals and only about 2.8% practice proper tooth brushing. This indicates that improvement in the oral and dental health of the Indonesian people is still needed. The aim of this activity was to improve the oral and dental health of the community. The method used was an educational session using dental stand media as part of the World Oral Health Day 2024 commemoration at SD Muhammadiyah Tamantirto, Yogyakarta. To measure the success of the activity, pre-tests and post-tests were conducted. The results of the activity showed an increase in the knowledge of oral and dental health and the skills of children in oral hygiene through tooth brushing in grade 3 students by 3% and in grade 4 students by 2.7%. The conclusion of this activity is that promotive and preventive dental actions provide significant benefits to the community and after the counseling, there was an increase in understanding of oral and dental health.